The Analysis of the Level of the Students’ Reading Comprehension by Using Barrett Taxonomy in SMAN 1 Lubuk Alung - Annisa Krismadayanti; Yetti Zainil (Journal of English Language Teaching, 2021)
The Industrial Revolution 4.0 created new changes in education system in Indonesia. Education is demanded to fulfill standardization. The students are also demanded to have good ability in reading comprehension. This study is aimed to find out the level of the students’ reading comprehension in narrative text by using Barrett’s taxonomy in SMAN 1 Lubuk Alung. The population was the eleventh grade students in academic year 2021/2022 who have learned narrative text in tenth grade with the total 359 students. Based on the population, the sample of this research is two classes consisted of 80 students selected using cluster random sampling. This research is descriptive quantitative research and used test and questionnaire as the instruments. This research found that the mean of the students’ score was 64.525 and it was categorized in good category. Besides that, the students have good ability in answering the questions in form of appreciation level. This study also found that students tent to have difficulty in answering questions in form of evaluation level.